Effects of Bovine Plasma and Pharmacological Zinc Level on Nursery Pig Growth Performance and Fecal Characteristics - Zhong-Xing Rao; Mike D. Tokach; Jason C. Woodworth; Joel M. DeRouchey; Robert D. Goodband; Joy M. Campbell; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2022)
A total of 300 pigs (241 × 600, DNA; initially 12.9 lb) were used in a 38-d trial to evaluate the effect of Zn level and bovine plasma in nursery pig diets. At the time of placement, pens of pigs were weighed and allotted to 1 of 4 dietary treatments in a randomized complete block design with barn as the blocking factor. There was a total of 60 pens with 5 pigs per pen and 15 replicates per dietary treatment. The treatments were arranged in a 2 × 2 factorial with main effects of Zn level (high and low) and spray-dried bovine plasma inclusion (with or without; APC Inc., Ankeny, IA). Diets with pharmacological levels of Zn had 3,000 and 2,000 ppm of Zn in phase 1 and 2 diets, respectively. Diets with low level of Zn had 110 ppm of Zn in phase 1 and 2 diets. Bovine plasma replaced a portion of a fermented vegetable protein source (MEpro, Prairie Aquatech, Brookings, SD) in diet formulation with bovine plasma included at 5% and 2% in the phase 1 and 2 diets, respectively. Treatment diets were fed in 2 phases (phase 1: d 0 to 9; phase 2: d 9 to 24) with a common diet (110 ppm of Zn without plasma) fed from d 24 to 38. Fecal samples and scores were collected on d 9 and 24 for determination of fecal dry matter. There was no evidence of Zn × plasma interactions (P>0.10) throughout the trial for any growth criteria. From d 0 to 9, pigs fed bovine plasma tended to have improved ADG (P =0.066) and had improved (P ≤0.035) ADFI and BW, while pigs fed high Zn had improved (P ≤0.018) ADG, BW and F/G. From d 9 to 24, pig fed high Zn had improved (P<0.001) ADG and ADFI. During the common period (d 24 to 38), pigs previously fed high Zn had reduced ADFI (P =0.046). Overall (d 0 to 38), pigs fed high Zn had improved (P ≤0.029) BW, ADG, and F/G. For fecal DM, there was a tendency of plasma × Zn interaction (P= 0.067) where pigs fed high Zn had increased (P<0.05) fecal DM compared to pigs fed low Zn when bovine plasma was added, while this Zn effect was not significant (P>0.05) when fed in diets without plasma. For fecal score, pigs fed high Zn had higher (P<0.001) frequency of firmer feces. In summary, bovine plasma improved growth performance during the first week after weaning. Feeding pharmacological levels of Zn improved growth performance when fed and overall, as well as improved fecal DM and fecal firmness measured by observational scoring.
Keywords: fecal characteristics; growth; nursery pigs; plasma; zinc